2005
DOI: 10.1038/sj.ijo.0803045
|View full text |Cite
|
Sign up to set email alerts
|

Milk intake is inversely related to obesity in men and in young women: data from the Portuguese Health Interview Survey 1998–1999

Abstract: Objective: To assess the relationships between milk intake and body mass index (BMI) in a representative sample of the mainland Portuguese population. Design: Cross-sectional study. Setting: National Health Interview Survey 1998-1999. Average daily milk intake was calculated by a frequency questionnaire that also assessed the average volume of one serving. BMI was derived from the subject's reported height and weight. Subjects: A total of 17 771 men and 19 742 women aged X18 y. Results: In men, milk intake was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 25 publications
7
46
1
1
Order By: Relevance
“…Interestingly, and contrary to an American study (Popkin et al, 2003), the highest increase in milk intake was observed in the less well-educated group. Overall, our data indicate that the milk (and thus calcium) intake of the Portuguese population is improving, with possible beneficial effects on cardiovascular risk factors (Zemel, 2001;Reid et al, 2002;Schröder et al, 2002) and obesity, as several studies have shown that increased milk or dairy products intake is inversely related to obesity (Mirmiran et al, 2005;Marques-Vidal et al, 2006).…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, and contrary to an American study (Popkin et al, 2003), the highest increase in milk intake was observed in the less well-educated group. Overall, our data indicate that the milk (and thus calcium) intake of the Portuguese population is improving, with possible beneficial effects on cardiovascular risk factors (Zemel, 2001;Reid et al, 2002;Schröder et al, 2002) and obesity, as several studies have shown that increased milk or dairy products intake is inversely related to obesity (Mirmiran et al, 2005;Marques-Vidal et al, 2006).…”
Section: Discussionsupporting
confidence: 58%
“…Assessment of functional food consumption FF, which were selected according to a list (42) , were taken from the FFQ. Moreover, modified milk (milk with low/ reduced fat, milk with added n-3), infusions (coffee and tea) and soya milk were considered as FF in this review, due to various studies that reported these foods might reduce the risk of some diseases (43)(44)(45)(46)(47)(48)(49) .…”
Section: Dietary Questionnairementioning
confidence: 99%
“…High fat snacks and sugar-rich drinks provide a tremendous amount of energy, thus frequent consumption of unhealthy snacks is mentioned as a potential cause of obesity (10). On the other hand, results of many studies suggest that decreasing milk or dairy consumption my lead to increased body fat and obesity (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%